Exploiting Le Chatelier's principle for a one-pot synthesis of nontoxic HHogGNPs with the sharpest nanoscopic features suitable for tunable plasmon spectroscopy and high throughput SERS sensing. Issue 75 (7th September 2017) - Bhattacharya, M.; Mazov, V.; Satpati, B.; Jena, P.; Das Chakraborty, S.; Kumar, S.; Pathak, B.; Kuznetsov, D. V.; Senapati, D.
Abstract : Le Chatelier's principle leads to the generation of nontoxic, stable and highly anisotropic HHogGNPs. Abstract : Applying Le Chatelier's principle, a one-pot synthesis method is reported that generates highly anisotropic hedgehog gold nanoparticles (HHogGNPs), undemanding of a preformed seed or surfactant. These non-toxic HHogGNPs are potent candidates for nanomedicinal applications owing to their broad-band plasmon tunability, gigantic Raman enhancement and remarkable retention in a highly salted physiological environment.